2019
DOI: 10.1002/adom.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Si/CuIn0.7Ga0.3Se2 Core–Shell Heterojunction for Sensitive and Self‐Driven UV–vis–NIR Broadband Photodetector

Abstract: to the high conductivity and transparency of graphene. [8] Nevertheless, high dark current arising from the gapless of graphene is detrimental to the responsivity and detectivity of this hybrid system. Si/ metal sulfide system suffers from severe recombination due to a large number of trap defects in low-crystalline sulfides that are grown by the hydrothermal or solvothermal processes. [9] Therefore, it is essential to develop promising semiconductors to couple with Si to enhance the photoelectric performance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…The device exhibits a broadband responsivity ranging from 300 to 1100 nm. The maximum responsivity is found to be ∼414 mA W −1 at ∼800 nm, which is higher than those of the recently reported Si/ CIGS core−shell heterojunction, 24 graphene/planar-Si Schottky diode 41 and far larger than Si/perovskite core−shell heterojunctions. 23 Apparently, the observed excellent spectral response without any exterior power supply confirms that the built-in electric field efficiently separates the photogenerated carriers in the space charge region.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…The device exhibits a broadband responsivity ranging from 300 to 1100 nm. The maximum responsivity is found to be ∼414 mA W −1 at ∼800 nm, which is higher than those of the recently reported Si/ CIGS core−shell heterojunction, 24 graphene/planar-Si Schottky diode 41 and far larger than Si/perovskite core−shell heterojunctions. 23 Apparently, the observed excellent spectral response without any exterior power supply confirms that the built-in electric field efficiently separates the photogenerated carriers in the space charge region.…”
Section: Resultscontrasting
confidence: 56%
“…Thus, it is important to design a novel semiconductor to integrate with Si to enrich the photoresponse characteristics. For instance, Chen et al 24 reported the fabrication of a Si/CuIn x Ga 1−x Se 2 (CIGS) core/shell heterojunction and demonstrated its admirable photodetection characteristics. However, the fabricated device is limited to photodetection applications only.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 6d, after the contact, the Fermi level equilibrium could be achieved in the interface due to the migration of electrons, and the band edges of each component near the contact interface bend, theoretically capable of forming a gradient energy band configuration. 42,43 Such an energy band configuration could accelerate the photogenerated hole transport from the ZnO core to CdS and Ag 2 S, thus increasing the reaction chance between the photogenerated holes and electrolyte, and decreasing the recombination of photogenerated charge carriers. 7f).…”
Section: Resultsmentioning
confidence: 99%
“…Several remarkable strategies have been employed to enhance the sensing performance of OSC‐based chemical sensors such as designing novel molecular structures, adding specific receptors on OSCs film, and modifying the film thicknesses . In addition, one‐dimensional (1D) materials with unique nanostructure (nanofiber, nanobelt, and nanotube) are suitable for low‐concentration detection, which offer high sensitivity and fast response time for chemical sensors because of the large surface‐to‐volume ratios in 1D materials.…”
Section: Introductionmentioning
confidence: 99%
“…31 Several remarkable strategies have been employed to enhance the sensing performance of OSC-based chemical sensors such as designing novel molecular structures, adding specific receptors on OSCs film, and modifying the film thicknesses. [32][33][34][35][36][37] In addition, one-dimensional (1D) materials with unique nanostructure (nanofiber, nanobelt, and nanotube) are suitable for low-concentration detection, which offer high sensitivity and fast response time for chemical sensors because of the large surface-to-volume ratios in 1D materials. Numerous synthetic methods have been developed to prepare 1D structured nanofibers of which electrospinning is a simple, fast, and cost-effective approach to fabricate nanowire materials by electrostatic stretching.…”
Section: Introductionmentioning
confidence: 99%